Pengembangan Prototipe Aplikasi Campus Tour Interaktif pada Metaverse (IJM: Journal of Multidisiplinary, 2025)
The advancement of metaverse technology has opened up new horizons in how humans interact with the digital world, particularly in the delivery of information and virtual experiences in the field of education. One of the most promising breakthroughs is the development of an interactive Campus Tour prototype application based on the metaverse, designed as an innovative way to introduce the campus environment in a comprehensive and engaging manner. This application targets prospective students, parents, and the general public who wish to get a closer look at the campus atmosphere and facilities without the need for a physical visit. The research adopts a design and development approach that includes user needs analysis, intuitive digital interface design, the implementation of a realistic 3D virtual environment, and initial user experience testing for comfort and usability. The development results demonstrate that users can enjoy an immersive campus tour through avatar features, narrated audio guides, and free navigation within the virtual campus setting. This innovation not only enhances the promotional strategy of educational institutions but also serves as an effective solution for prospective students who face geographical or mobility limitations, enabling them to experience the campus atmosphere directly through an advanced and captivating digital form.